Compressibility behavior of tropical peat - Youventharan Duraisamy (Kuantan, Pahang : Publisher Universiti Malaysia Pahang, 2010)
Compilation of author's presentation papers on the compressibility behavior of tropical peat
Keywords: Peat soils -- Tropics -- Congresses; Soil mechanics -- Congresses